1984
DOI: 10.1002/ep.670030215
|View full text |Cite
|
Sign up to set email alerts
|

Surface area of calcium oxide and kinetics of calcium sulfide formation

Abstract: Recent studies [ I ] suggest that a 50 percent reduction in emissions of SO2 and NO, may be necessary to avoid environmental damage by acid deposition. The US. Environ-18, 607-18 (1979). Robert H. Borgwardt is a Chemical Engineer with EPA's Office ofResearch and Development where he has responsibilities for in-house evaluation of processes for controlling sulfur emissions from coal combustion. In addition to hasic research, he was extensively involved in pilot scale development of the limestone wet scrubbing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
2

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 9 publications
(5 reference statements)
7
62
2
Order By: Relevance
“…Chemical compositions of various limestones can be found in Chan et al (1970), Chang et al (1984), Borgwardt and Roache (1984), Borgwardt et al (1987), and Fuller et al (1987). The specific· surface area of most of the8.e stones is low (generally less than 1m 2 /g) and the natural porosity ranges from 0 to 8% (Borgwardt and Roache, 1984;Hartman et al, 1978;Borgwardt et al, 1987). Whereas limestones are considered amorphous, Scanning Electron…”
Section: 1) Limestonementioning
confidence: 99%
“…Chemical compositions of various limestones can be found in Chan et al (1970), Chang et al (1984), Borgwardt and Roache (1984), Borgwardt et al (1987), and Fuller et al (1987). The specific· surface area of most of the8.e stones is low (generally less than 1m 2 /g) and the natural porosity ranges from 0 to 8% (Borgwardt and Roache, 1984;Hartman et al, 1978;Borgwardt et al, 1987). Whereas limestones are considered amorphous, Scanning Electron…”
Section: 1) Limestonementioning
confidence: 99%
“…The first by Borgwardt 47 showed that for micrometer size particles of CaO the rate of CaS formation is most probably limited by diffusion through the product layer surrounding individual CaO grains.…”
Section: Development Of a Model For The Absorption Processmentioning
confidence: 99%
“…Studies of S O 2 removal at high pressures have been carried out both with carbonates and precalcined solids Newby et al, 1980;Ulerich et al, 1982; Hayhurst, 1984, 1987;Bulewicz et al, 1986. However, because of the aforementioned complexities, with the exception of the general conclusion that favorable desulfurization is possible under PFBC conditions, there is not much agreement in the literature on the e ects of the various -4-parameters on the process.…”
Section: Background Informationmentioning
confidence: 99%
“…Hayhurst 1984, 1987, for example, found that the reaction rate of precalcined limestones in a uidized-bed reactor decreases with an increase in the operating pressure, both in the absence and presence of C O 2 . W orking with a laboratory-size PFBC, Bulewicz et al 1986 observed an increase in the sorption capacity of C a -based sorbents chalk, limestone, and dolomite with an increase in pressure up to 2 atm, but further increase in pressure caused a reduction in the sorption capacity of all samples. Similar observations were made by Jansson et al 1982.…”
mentioning
confidence: 97%
See 1 more Smart Citation